Building reading resilience : developing a skills-based approach to literary studies : final report 2012. - Kennedy, Rosanne; Douglas, Kate; Poletti, Anna; Seaboyer, Judith; Barnett, Tully (Office for Learning and Teaching, Department of Industry, Innovation, Climate Change, Science, Research and Tertiary Education, 2012)
The ability to read and comprehend a range of complex texts is recognised as a foundation skill and required outcome for students in literary studies, and this is commonly expressed in learning objectives. It also has wide applicability outside the university, in the worlds of business, education, government and politics. Many academics have noted, however, that it is increasingly difficult to engage students in the task of reading demanding texts in the tertiary literary studies classroom (Clausson, Chance, Gallop, Scholes). Students often come to class without having completed the required reading, which impacts on their ability to develop advanced skills of literary comprehension and analysis. Moreover, the failure to complete assigned reading impacts on curriculum development and teaching quality in ways that are not clearly articulated, and are commonly dealt with in ad-hoc ways by individuals or small groups of staff. Robert Scholes, recent President of the Modern Language Association and a leader in the field of literary pedagogy, contends that the decline in reading skills has slipped under the radar. The challenges associated with reading literary texts today, in an environment in which students have many demands on their time – ranging from outside work and family commitments to new digital technologies – are not well understood. Nor is there currently, in Australia, a profession-wide discussion of the problems and potential strategies for addressing these problems. The Reading Resilience Toolkit, the major outcome of this project, introduces a new approach to teaching reading skills and provides resources to address problems in delivering undergraduate literature curricula. [Executive summary]